Biobanking of a Marine Invertebrate Model Organism: The Sea Urchin - Estefania Paredes (Journal of Marine Science and Engineering, 2016)
The sea urchin has long been used as an invertebrate model organism in developmental biology, membrane transport and sperm oocyte interactions, and for the assessment of marine pollution. This review explores the effects of cryopreservation and biobanking in the biology and development of sea urchins, all the way from germaplasm through to juveniles. This review will provide an integral view of the process and all that is known so far about the biology of cryopreserved sea urchins, as well as provide an insight on the applications of the biobanking of these model organisms.